2016
DOI: 10.1111/jsap.12474
|View full text |Cite
|
Sign up to set email alerts
|

A magnetic resonance imaging‐based classification system for indication of trans‐sphenoidal hypophysectomy in canine pituitary‐dependent hypercortisolism

Abstract: Dogs with Type A, Grade 1 to 3 hyperadrenocorticism had a good prognosis following trans-sphenoidal hypophysectomy. Grade 3B, 4 and 5 cases may not be suitable for this surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 21 publications
3
30
0
Order By: Relevance
“…Thus, Sato reported on an MRI-based classification system using the pituitary tumor sizes in PDH cases. 29 The system is used to classify cases to grades I-V based on the size of the pituitary tumor and positional relationships between the pituitary tumor and the cranial structure and to determine whether blood vessels are involved (A or B). Sato et al reported that the pituitary tumor was completely removed in 29 (93.5%) of 31 total PDH cases corresponding to grades I-IIIA.…”
Section: B Amentioning
confidence: 99%
See 4 more Smart Citations
“…Thus, Sato reported on an MRI-based classification system using the pituitary tumor sizes in PDH cases. 29 The system is used to classify cases to grades I-V based on the size of the pituitary tumor and positional relationships between the pituitary tumor and the cranial structure and to determine whether blood vessels are involved (A or B). Sato et al reported that the pituitary tumor was completely removed in 29 (93.5%) of 31 total PDH cases corresponding to grades I-IIIA.…”
Section: B Amentioning
confidence: 99%
“…6,33,34 Furthermore, plasma ACTH concentration and UCCR are useful not only in clinical diagnosis but also for post-TSS recurrence and post-treatment monitoring. 22,29,35…”
Section: Acthmentioning
confidence: 99%
See 3 more Smart Citations